Nutritional parameters of individuals with COVID-19 hospitalized in ICU (Research, Society and Development, 2021)
As it is a disease that mainly affects the respiratory system, COVID-19 can evolve into a more critical situation, even leading to multiple organ failure, even fatal. Conditions in which acute respiratory complications require prolonged stay in Intensive Care Units (ICUs) are the main causes of morbidity and mortality in patients with COVID-19. The stay in the ICU, especially for a long time, is, by itself, a cause of changes in nutritional parameters. In view of this, this study aims to analyze the behavior of the nutritional status and parameters of patients with COVID-19 admitted to the ICU during the course of the pandemic. An integrative literature review was carried out, in which a systematic method was used for the synthesis and analysis of available scientific papers. It was found that, in cases of aggravated COVID-19 patients undergoing treatment in the ICU, there was a significant presence of comorbidities such as diabetes, hypertension and their association among hospitalized individuals, as well as changes in the profile of caloric and protein intake and in the nitrogen balance. It was also found that malnutrition and moderate to high nutritional risk were considered risk factors for longer hospital stays. The possibility of investigating more detailed parameters is crossed by the pandemic context itself, in which the urgency of patient management and the need for isolation and adoption of sanitary protocols often make it impossible to carry out scientific research with critically ill patients due to COVID-19.